FAMILY CENTERED MATERNITY CARE (FCMC) SEBAGAI SALAH SATU UPAYA SKRINING / DETEKSI DINI RESIKO TINGGI IBU HAMIL BERBASIS KELUARGA DI DESA DANGURAN - Henik Istikhomah (P3M Universitas Aisyiyah Surakarta, 2018)
Family centered maternity care (FCMC) activity in high-risk pregnancy is one of the high risk screening / early detection of family-based pregnant women because it gets full support and involvement from all family members. This activity aims to improve the ability of the family as a companion of pregnant women in suppressing maternal mortality. With the introduction of Family Centered Maternity Care (FCMC) activities, family knowledge and ability in early detection and promotive efforts in high-risk pregnancy cases increases. With family awareness and ability to monitor pregnant women's health, it can make it easier for cadres and midwives to make early detection of pregnancy at risk.Â Â